Integration of Forest and Climate Change Policies in Nepal - Paudel, Ganesh; Adhikari, Shankar; Bhusal, Prabin (Journal of Forest and Natural Resource Management, 2019)
Climate change poses threats to forest ecosystems, forest dependent communities and society as a whole. Incorporation of climate change in forest policy and vice-versa is essential to effectively deal with climate change impacts while managing forest. Review of climate change and forest policies, incorporating forestry and climate change issues has not been substantially discussed and analyzed yet in Nepal. In this paper we aim to review the climate change and forest policies in terms of its content, relevancy and adequacy. We reviewed five forest policies and three climate change related plans and policies regarding integration of forest and climate change issues in respective policies. Our review reveals that forest policies contain notable provisions in regard to the contribution of forestry to climate change mitigation and adaptation. However, new and emerging issues such as climate refugia and invasive species are least concerned in forest policies. Climate change policies also contain provisions for forest management focusing on the mobilization of forest user groups for carrying out adaptation activities at the local level. However, the implementation of both polices seems poor due to lack of legal framework. Therefore, formulation of legal framework for implementation of these policies is essential. Similarly, we suggest both policies need to be revised incorporating the provisions based on scientific findings and field experience.